The Theology of Martin Luther : A Critical Assessment - Barth, Hans-Martin (Book collections on Project MUSE., 2012)
Does Martin Luther have anything to say to us today? Nearly five-hundred years after the beginning of the Reformation, Hans-Martin Barth explores that question in this comprehensive and critical evaluation of Luther's theology. Rich in its extent and in its many facets, Barth's didactically well-planned work begins with clarifications about obsolete and outdated images of Luther that could obstruct access to the Reformer-for example, the question of the Peasants' War and Luther's attitude toward other religions and superstition. The second part covers the whole of Martin Luther's theology. Hav.